Draft genome and description of Merdibacter massiliensis gen.nov., sp. nov., a new bacterium genus isolated from the human ileum - Anani, Hussein (Sci Rep, 2019)
We used phenotypic, genomic and phylogenetic information following the taxono-genomics approach to demonstrate that strain Marseille–P3254, isolated from an ileal sample of a 76-year old woman who underwent upper and lower digestive tract endoscopy for esophagitis and colonic polyp, is representative of a novel bacterial genus within the family Erysipelotrichaceae in the phylum Firmicutes. It is an anaerobic Gram-negative bacterium without catalase and oxidase activities. The genome of strain Marseille–P3254 is 2,468,496-bp long with a 40.1% G + C content. This new bacterium is most closely related to Eubacterium dolichum, with which it shares 90.7% 16S rRNA sequence similarity. In addition, genomic comparison using the digital DNA–DNA hybridization and OrthoANI analyses between the novel organism and the E. dolichum type strain revealed identities of 25.2 and 68.91%, respectively. The major fatty acids were C(16: 0), C(18: 1n9) and C(18: 0). Based on these data, we propose the creation of the new genus Merdibacter gen. nov., with strain Marseille-P3254(T) (=CSUR P3254 = DSM 103534) being the type strain of the new species Merdibacter massiliensis gen. nov., sp. nov.